(untitled) (Economics and region, 2019)
The purpose of the article is to study the characteristics of managing tourism enterprises in the face of increased threats. The authors examined the main indicators of the development of the tourism business in different countries of the world. The threats and dangers that affect not only the management system of tourism enterprises, but also their safety are also investigated. As a result of the study, the authors identified the main threats and dangers of subjects of tourism activities that arise during the functioning of tourism enterprises and associated with the shortcomings in the management of material, informational, human, financial and other resources of tourism enterprises. In the process of research, a business growth model is proposed that can be used to manage a tourism business enterprise in an environment with a high level of danger. According to the authors, the set of management components at each stage of the development of the company must be adequate to its internal and external environment, otherwise the effectiveness of the company will decrease. Prospects for further research is to identify potential areas for minimizing risks and threats, will provide not only an appropriate level of competitiveness of a tourism company, but also its development..